The Needs of Parents of Children Suffering from Cancer-Continuation of Research - Anna Lewandowska (MDPI AG, 2022)
Background: Parents experience many healthcare needs when caring for their sick children. Research shows that parents of oncological children have a high level of unmet needs, including psychosocial, emotional, physical, informational, financial, educational, and spiritual needs. To date, little quantitative research has been carried out on the specific needs of parents of children with cancer, which creates uncertainty about what areas should be addressed in care. This study investigated the prevalence of unmet needs among parents of children with cancer. Methods: A population survey was conducted between 2015 and 2020. Caregivers of children diagnosed with cancer were invited to participate in the study to assess their problems and needs. Results: The analysis found that 97% of the participants experienced some level of need for one or more items, and 73% of the respondents reported a moderate or high need for one or more items. In the field of medical information, 70% of respondents had moderate or high needs, 55% of parents reported a moderate or high level of need for help in the psychological or emotional field, and 30% in the financial domain. The prevalence of moderate or high need in the remaining domains ranged from 10% to 15%. Conclusions: Parents of children with cancer experience a high level of needs, especially psychological, emotional, and information. These data suggest that the existing healthcare system does not meet the needs of parents of sick children. The results show the need to investigate the mechanisms by which healthcare providers can use the healthcare system to identify and meet needs.